2018
DOI: 10.1002/advs.201800747
|View full text |Cite
|
Sign up to set email alerts
|

4,5‐Diazafluorene‐Based Donor–Acceptor Small Molecules as Charge Trapping Elements for Tunable Nonvolatile Organic Transistor Memory

Abstract: Three diazafluorene derivatives triphenylamine (TPA)(PDAF)n (n = 1, 2, 3) serving as small molecular elements are designed and synthesized via concentrated sulfuric acid mediated Friedel–Crafts reaction. With highly nonplanar topological configuration, TPA(PDAF)3 shows weaker intermolecular interaction in the solid states and thus exhibits single nanomolecular behavior, which is crucial for charge stored and retained in an organic field‐effect transistor (OFET) memory device. Furthermore, diazafluorene derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 49 publications
0
43
0
1
Order By: Relevance
“…Organic materials have tunable properties by easy modification of chemical and physical structures . In addition, it is compatible with the solution process that enables facile and scalable fabrication.…”
mentioning
confidence: 99%
“…Organic materials have tunable properties by easy modification of chemical and physical structures . In addition, it is compatible with the solution process that enables facile and scalable fabrication.…”
mentioning
confidence: 99%
“…在电场诱导作用下, 苯基芴位阻基团发生 构象变化. 该变化会阻止PVK上的咔唑单元π-π堆积, [44] . TPA(PDAF) 3 筑分子建筑与分子窗格的重要基元, 探索其跨尺度合 成以及有机智能的纳米分子集成平台将成为重要的研 究方向 [73] .…”
Section: 聚合物类Cdafsunclassified
“…47 Subsequently, the application of electrets in OFET memory has developed rapidly. [48][49][50] Charges trapped in polymer electrets can be generated by the following mechanisms: (i) charges trapped by structural defects and impurity centers; (ii) orientation of dipoles (in polar materials); and (iii) build-up of charges near heterogeneities such as grain boundaries (in polycrystalline materials) and amorphous-crystalline interfaces (in semicrystalline polymers). 51 In 2008, Kim and co-workers systematically studied the characteristics of various polymer electrets, 51 and concluded that only non-polar and hydrophobic polymers could be used as effective dielectrics, acting like floating gates in floating gate memories.…”
Section: Polymer Electret Ofet Memorymentioning
confidence: 99%